A bi-block sleeper dynamic strain monitoring method based on embedded FRP-OF sensor. (2nd May 2022) - Li, Peigang; Lan, Caihao; Liu, Zengjie; Li, Junqi; Wu, Weifan; Wang, Jian; Wang, Xianjin; Qiu, Jihong; Liu, Dan
Highlights: The FRP-OF strain sensors are embedded inside the sleeper for a long-term monitoring. The linearity of the sleeper internal strain and applied load has been found. The distribution ratio of wheel load on sleeper have been explored and verified. The difference of sleeper response is studied when different vehicles passed. A supplementary means for monitoring the rail seat force and wheel/rail force. Abstract: The traditional surface contact monitoring, in which sensors and wires are exposed outside, has a great risk on long-term monitoring at high-speed railway (HSR). This paper proposed a method that embedding the Fiber Reinforced Polymer-Optical Fiber (FRP-OF) sensor into the bi-block sleeper, which was designed for long-term monitoring of sleeper dynamic strain at high-speed railway. Sleeper is the key component of bi-block ballastless track that bears and transmits the load from wheel. Its internal dynamic strain somehow reflects the wheel/rail force under the high-speed train load. Considering the symmetry of bi-block sleeper, a single block of sleeper was selected for this research. To validate the feasibility of monitoring sleeper strain by embedding FRP-OF sensor in sleeper, both laboratory static test and field dynamic test have been conducted. The results showed that there was a linear relationship between the sensor response and the applied load in the laboratory static test. The wheel load ratio assigned to each sleeper and the mechanical behavior is verified theoretically and experimentally. The single wheel load is mainly borne by five sleepers below the rail, which bearing 8%, 22%, 32%, 22%, 8%. Then, the load of different train can be sensed by the sensors in the field dynamic test, which clearly identified the process of wheel action and showed good repeatability. The dynamic strain in sleeper was about 3-7με with 150kN axle load at 350 km/h, which was converted to rail seat force of 33-35kN, and 7-18με with 230kN axle load at 160 km/h which was converted to rail seat force of 89-96kN. The impact factors on the track are different since the difference of the vechicles load. In general, the vertical transient strain level of sleeper is low, but the trend of strain variation is obvious and accords with the characteristics of wheel load distribution ratio. It can be seen that the sensors had good performance on dynamic strain monitoring of bi-block sleeper, which will be used as the important supplementary means of the future wheel/rail force monitoring.